[PP.20.01] LCZ696 THERAPY IS ASSOCIATED WITH IMPROVEMENT OF VENTRICULAR ARTERIAL COUPLING AND WORK EFFICIENCY IN PATIENTS WITH HEART FAILURE AND REDUCED EJECTION FRACTION. (September 2016) - Kobalava, Z.; Babaeva, L.; Lukina, O.; Zharikova, E.; Tyukhmenev, E.; Villevalde, S.
Abstract : Objective: Angiotensin receptor-neprilysin inhibition with LCZ696 is a novel approach for the treatment of heart failure with reduced ejection fraction (HFrEF). The aim of the study was to assess the effects of valsartan/sacubitril on parameters of ventricular-arterial coupling and left ventricular (LV) work efficiency in patients with stable HFrEF. Design and method: In the open-label follow-up to PARADIGM HF study 18 patients with stable HFrEF (16 male, 69 ± 9 years (M ± SD), arterial hypertension 83%, previous myocardial infarction 89%, diabetes mellitus 39%, dyslipidemia 56%, LVEF 32 ± 4%, serum creatinine 118 ± 21 μmol/l, eGFR 56 ± 13 ml/min/1.73m 2, potassium 4.45 ± 0.35 mmol/l) were enrolled. Patients received a stable background treatment for at least a month (ACEI 94%, beta-blockers 100%, aldosterone receptor antagonists 83.3%, loop diuretics 72.2%). ACEI treatment was interrupted for 36 h and replaced with LCZ696 100 or 200 mg (11 patients) BID according to baseline brachial BP (mean dose 185.7 ± 36.3 mg BID). 2-dimentional echocardiography was performed to assess arterial (Ea) and end-systolic LV elastance (Ees) baseline and after 6 month LCZ696 therapy. VAC was assessed as the ratio Ea/Ees. Wilcoxon test was considered significant if p < 0.05. Results: Baseline brachial BP decreased from 137.1 ± 22.0/83.4 ± 11.8 to 120.5 ± 13.5/75.1 ± 9.3 mmHg (δ -16.6 ± 14.2/−8.3 ± 10.3 mmHg, p < 0.05), heart rate did not change (78 ± 12 vs 75 ± 15 beats/min (δ −2.7 ± 14.7 beats/min, p > 0.05). LCZ696 therapy was associated with significant decrease of VAC (2.10 ± 0.55 vs 1.68 ± 0.32, p < 0.05), Ea (2.11 ± 1.04 vs 1.66 ± 0.6 mmHg/ml/m 2 (δ -0, 70 (-0.26%)), p < 0.05), arterial peripheral resistance (0.029 ± 0.016 vs 0.027 ± 0.011 mmHg/ml/min, p < 0.05), increase of stroke volume (63 ± 24 vs 78 ± 26 ml, p < 0.05). Ees remained unchanged (1.11 ± 0.42 vs 1.01 ± 0.52 mmHg/ml/m 2, p > 0.05). LCZ696 therapy was associated with potential energy decrease (8049 ± 2846 vs 5037 ± 2492 mmHg*ml/m 2, p < 0.05), stroke work/pressure-volume area index (LV work efficiency) increase (0.48 ± 0.09 vs 0.63 ± 0.05, p < 0.05). There was no statistically significant correlation between decrease of Ea and brachial BP decrease. LCZ696 was well tolerated and there were no BP-related adverse events. Conclusions: In stable patients with HFrEF LCZ696 therapy was associated with BP-independent improvement in VAC related with decrease of Ea rather than Ees changes. Treatment with LCZ696 was also associated with decrease of arterial peripheral resistance and improvement of LV work efficiency